Technological Ecosystems That Support People With Disabilities: Multiple Case Studies - Ramirez-Montoya, Maria Soledad; Anton-Ares, Paloma; Monzon-Gonzalez, Javier (Frontiers in Psychology, 2021)
Advances in technology, research development, and teaching practices have brought improvements in the training, levels of autonomy, and quality of life of people who need support and resources appropriate to their circumstances of disability. This article focuses on empirically analyzing the usefulness of treatments that have been supported by technology to answer the question, "How do technological ecosystems being used help people with special educational needs?" The multiple case study methodology was used to address six categories of analysis: project data, objectives, processes, outputs and outcomes, technologies, and impact. The processes, open in communication, were characterized as transversal, ethical, and sustainable. The results yielded various technological ecosystems that support people with disabilities and deliver the help they need to improve their health and provide enjoyable user experiences.